TEST CHARACTERISTICS OF THE TURBINE SAVONIUS 4 LEVELS SECTIONAL, PARTITIONED, 0.25 DIAMETER OVERLAP AND 45o SLIDING ANGLE WITH COMPARABLE STANDARD TURBINE - Sudargana, Sudargana; Yunianto, Bambang; M., Abiseka; Utomo, Teguh Priyo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2014)
The energy and environmental crisis where CO2 causes global warming and climate change. This condition encourage the world community take advantage of new renewable energy non-CO2 as wind, water currents, geothermal, solar, etc. Savonius Turbine has a simple construction can be made by the public so they can be used for wind power or hydro countryside. In this study aims to improve the efficiency and reduce the amplitude of vibrations to the modification of the 4-storey Savonius turbine, partitioned, sliding angle 45 degree and 0.25 diameter blade overlap. The location of research is Cokro Tulung Channel Klaten and Parangrucuk Baron Beach Gunungkidul. Measurements such as water current and wind speed, turbine rotational speed, torque of the turbine shaft and power. The turbines analysis are torque, power and efficiency characteristics and comparing by the turbine Savonius standard (one pair of blades). Results as hydro turbine at low velocity 0.3166 m/s Savonius 4 level had better revolution and efficient (0.0826) than 1 level (0.024), but as wind turbine at 3.056 m/s velocity the Savonius 4 level had worse efficiency (0.039) than 1 level (0.025) because the inertia load